Understanding the personality of Europe’s only world surfing reserve - Martins A. F.; Penela, D.; Cardoso, M. G. M. S. (Consumer Behavior in Tourism and Hospitality, 2023)
Purpose: This study aims to uncover the destination personality of the World Surfing Reserve (WSR) in Europe, Ericeira, from local stakeholders’ perspectives; understand if WSR recognition influences the perception of destination personality; and understand if there is an alignment between the vision of the destination management Organization (DMO) and stakeholders in terms of destination personality. Design/methodology/approach: An extensive literature search was conducted to identify personality traits, which were then filtered and included in a survey of Ericeira's stakeholders and in a DMO interview. A principal components analysis enabled the identification of the most relevant personality traits. Findings: Cool, appealing and self-assured emerged as destination-specific personality traits of Ericeira, indicating that other similar destinations can consider them in future branding actions. The findings indicate that WSR recognition can be a determinant for local tourism but has no impact on destination personality as viewed by local stakeholders. Therefore, one can suggest that personality is embedded in a tourist destination and is somewhat resistant to external WSR recognition. In general, alignment was found between the views of the local stakeholders and the DMO. Originality/value: This study reinforces the literature on the importance of stakeholder involvement in place brand development. It also suggests that external recognition may have an impact on local tourism but has a limited impact on destination personality. Finally, this research constitutes a baseline for further studies on the destination personality traits of current and prospective